Extract of Woodfordia fruticosa flowers ameliorates hyperglycemia, oxidative stress and improves beta-cell function in streptozotocin-nicotinamide induced diabetic rats - Arya, Aditya; Al-Obaidi, M.M.J.; Karim, R.; Taha, H.; Khan, A.K.; Shahid, N.; Sayem, A.S.; Looi, C.Y.; Mustafa, Mohd Rais; Mohd, M.A.; Ali, Hapipah Mohd (Elsevier, 2015)
Ethnopharmacological relevance: The art of Ayurveda and the traditional healing system in India have reflected the ethnomedicinal importance of the plant Woodfordia fruticosa Kurtz, which demonstrates its vast usage in the Ayurvedic preparations as well as in the management of diabetes by the traditional healers. Aims of study: The study aimed to ascertain the antidiabetic potential of W. fruticosa flower methanolic extract (WF) on Streptozotocin (STZ)-nicotinamide-induced diabetic rat model. Materials and methods: Diabetes was induced in Sprague Dawley (SD) rats by STZ-nicotinamide and thereafter diabetic rats were treated with three different doses of WF (100, 200 and 400 mg/kg body weight) respectively and glibenclamide as a positive control. Biochemical parameters such as blood glucose, serum insulin and C-peptide levels were measured with oxidative stress markers. Furthermore, histology of liver and pancreas was carried out to evaluate glycogen content and beta-cell structures. Moreover, immunohistochemistry and western blot analysis were performed on kidney and pancreas tissues to determine renal Bcl-2, pancreatic insulin and glucose transporter (GLUT-2, 4) protein expression in all the experimental groups. Results: The acute toxicity study showed non-toxic nature of all the three doses of WF. Further, studies on diabetic rats exhibited anti-hyperglycemic effects by upregulating serum insulin and C-peptide levels. Similarly, WF shown to ameliorate oxidative stress by downregulating LPO levels and augmenting the antioxidant enzyme (ABTS). Furthermore, histopathological analysis demonstrate recovery in the structural degeneration of beta-cells mass of pancreas tissue with increase in the liver glycogen content of the diabetic rats. Interestingly, protective nature of the extract was further revealed by the immunohistochemical study result which displayed upregulation in the insulin and renal Bc1-2 expression, the anti apoptosis protein. Moreover, western blot result have shown slight alteration in the GLUT-2 and GLUT-4 protein expression with the highest dose of WFc treatment, that might have stimulated glucose uptake in the pancreas and played an important role in attenuating the blood glucose levels. Conclusion: The overall study result have demonstrated the potential of WF in the management of diabetes and its related complications, thus warrants further investigation on its major compounds with in depth mechanistic studies at molecular level. (C) 2015 Elsevier Ireland Ltd. All rights reserved.